2019
DOI: 10.1080/13607863.2019.1695740
|View full text |Cite
|
Sign up to set email alerts
|

Participation as means for adaptation in dementia: a conceptual model

Abstract: Objectives: There are a number of conceptual models of dementia, capturing a range of biopsychosocial factors. Few integrate the lived experience of dementia. The aim of this study was to develop a conceptualisation grounded in the first-hand accounts of living with the condition and reflecting its complexity. Method: The study was conducted within an explanatory, critical realist paradigm. An overarching narrative approach, informed by a previously completed systematic review and metasynthesis of research on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 70 publications
(94 reference statements)
0
2
0
Order By: Relevance
“…Gorska et al (35) examined the emerging experience of people living with dementia and found that their potential to adjust to continuous changes is influenced by access to and quality of both personal and contextual resources which remain in a constant, transactional relationship to each other. They later found the process of adaptation to be one that involved active participation through ongoing, dynamic and non-linear interactions between the adaptive capacity of a person with dementia and the adaptive capacity within the environment (36). Together these studies indicate the importance and value of considering people with dementia and their needs within the relationships and contexts of their larger environments.…”
Section: Beyond Biopsychosocial: Adding a Social Ecological Perspective To Dementia Carementioning
confidence: 97%
“…Gorska et al (35) examined the emerging experience of people living with dementia and found that their potential to adjust to continuous changes is influenced by access to and quality of both personal and contextual resources which remain in a constant, transactional relationship to each other. They later found the process of adaptation to be one that involved active participation through ongoing, dynamic and non-linear interactions between the adaptive capacity of a person with dementia and the adaptive capacity within the environment (36). Together these studies indicate the importance and value of considering people with dementia and their needs within the relationships and contexts of their larger environments.…”
Section: Beyond Biopsychosocial: Adding a Social Ecological Perspective To Dementia Carementioning
confidence: 97%
“…People are looking for more self-determination and opportunities to conduct activities on their own, to continue to learn new things and be creative, as well as feel useful to others, have social contacts and give meaning to life [ 16 ]. The capacity of people with dementia to be involved in daily activities depends on the match between the person’s and the environment’s adaptive capacity [ 17 ]. As a result, people might not be able to engage with an activity in its original form but be able to pursue it if it is modified and personalised to suit their skills [ 18 ].…”
Section: Introductionmentioning
confidence: 99%